2021
DOI: 10.1017/s1744133121000190
|View full text |Cite
|
Sign up to set email alerts
|

How to fairly allocate scarce medical resources? Controversial preferences of healthcare professionals with different personal characteristics

Abstract: The scarcity of medical resources is widely recognized, and therefore priority setting is inevitable. This study examines whether Portuguese healthcare professionals (physicians vs nurses): (i) share the moral guidance proposed by ethicists and (ii) attitudes toward prioritization criteria vary among individual and professional characteristics. A sample of 254 healthcare professionals were confronted with hypothetical prioritization scenarios involving two patients distinguished by personal or health character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…The uneven distribution of healthcare resources is a long-standing challenge in China. It is also prevalent in other countries (regions), such as the United States ( 9 ), Portugal ( 10 ), Japan ( 11 ), Kenya ( 12 ), and Southeast Asia ( 13 ). As the largest developing country with a vast land area and a large population, China faces the challenge of maximizing the provision of comprehensive health care services given the constraints on available healthcare resources ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The uneven distribution of healthcare resources is a long-standing challenge in China. It is also prevalent in other countries (regions), such as the United States ( 9 ), Portugal ( 10 ), Japan ( 11 ), Kenya ( 12 ), and Southeast Asia ( 13 ). As the largest developing country with a vast land area and a large population, China faces the challenge of maximizing the provision of comprehensive health care services given the constraints on available healthcare resources ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, it has been found that adequate healthcare resources are conducive to reducing child COVID-19 mortality and morbidity (7). Health professionals are able to provide quality health services to tuberculosis patients, improving their quality of life and health outcomes (8).…”
Section: Introductionmentioning
confidence: 99%
“…The United Nations ranks “good health and well-being” third among its 17 SDGs (Sustainable Development Goals) and proposes the goal of “ensuring universal access to well-being and health care and achieving universal health coverage” (SDG3) [ 5 ]. Health resources are scarce, basic, and public social services, and improving the spatial balance and equity of health resources is a vital target of governments and international organizations [ 6 , 7 ]. As the quality of life improves the population’s demand for health services, which is on the rise, leading to the fact that the capacity to supply health resources in many countries, especially in developing countries, it is facing great challenges against the background of increasingly high medical costs [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%